NEEDS ANALYSIS FOR THE DEVELOPMENT OF A UNITY-BASED EDUCATIONAL GAME APPLICATION ON THE FAVOURITE FOOD AND DRINKS TOPIC AT SMP NEGERI 2 SUNGAI LILIN - Zulhaidir; Syarifuddin; Vianty, Machdalena (UIN Alauddin Makassar, 2025)
This study aims to analyze the needs for developing a Unity-based educational game on the topic Favourite Food and Drinks in English language learning at SMP Negeri 2 Sungai Lilin. A descriptive qualitative approach was employed, involving two English teachers and 60 seventh-grade students as research subjects. Data were collected through interviews, observations, and needs analysis questionnaires, and analyzed using descriptive qualitative and simple quantitative methods. The findings reveal that the learning process is still dominated by conventional media such as textbooks and PowerPoint presentations, which have not effectively enhanced students’ motivation and active participation. Both teachers and students showed a high level of enthusiasm toward the use of interactive educational game-based learning media. The questionnaire results indicated an average needs score of 83.96%, categorized as very high, with the aesthetic aspect receiving the highest score (89.2%). These findings confirm that educational game-based media are highly relevant to improve students’ vocabulary mastery and communicative abilities. Therefore, the development of a Unity-based educational game is recommended as an innovative solution to create interactive, engaging, and meaningful English learning in the digital era.